Investigation of the single-phase immersion cold plate amid PAO-4 and Noah@3000A – An experimental approach and its numerical verification - Zhang, Yong-Dong; Lin, Yu-Chi; Wang, Chi-Chuan (International communications in heat and mass transfer, 2024)
This study investigates improving traditional immersion cooling systems by employing cold plates in single-phase immersion cooling with dielectric fluids (Noah@3000 A and PAO-4). Experimental and CFD methods explore various cold plate structures in a 1 U server with a TTV heat source. Flow rates range from 1 to 3 LPM, and configurations include side-open, fully enclosed, and dual-open designs. Results show that incorporating cold plates reduces fluid bypass, enhancing thermal performance. High-viscosity dielectric oil as a coolant yields substantial improvements (36.1% and 41.6% at low and high flow rates) compared to traditional systems. Thermal resistance decreases with higher flow rates, more notably for Noah@3000A. Immersing the cold plate in liquid enhances convective heat transfer, reducing thermal resistances by 7.2% and 9.4% for Noah@3000A and PAO-4 at low flow rates. Smaller fin pitch consistently lowers resistance by eliminating bypass. Outlet configuration significantly influences thermal resistance, with Enclosed cold plates showing the least performance for PAO-4 and dual-open cold plate yields the worst performance with Noah@3000A. Differences in heat transfer behavior between PAO-4 and Noah@3000A are linked to laminar and turbulent flow characteristics. These findings offer insights into optimizing immersion cooling systems, emphasizing the impact of fluid choice and cold plate design on thermal performance.